As we know that the formula for the Point slope form is,
(y – b) = m (x - a).
In our question the value of ‘a’ is 0 and value of ‘b’ is 0 and value of ‘m’ is 3, so we will put all these values in our equation to get the exact solution.
y – 0 = 3(x - 0),
y = 3x,
y - 3x = 0,
This is the required point Slope form.
Now for getting the standard form we need the value of coefficient of ‘x’ will be greater than zero, but in our point Slope form it is less than zero , so we will multiply by the minus sign in whole equation to get the standard equation,
-y + 3x = 0,
3x – y = 0,
Here the value of ‘A’ is 3, the value of ‘B’ is -1 and value of ‘C’ is 0.
This is the required solution for the question.